Line x Tester Analysis in Pearl MilIet - Sabbarwal, P S; Nijhawan, D C (Annals of Arid Zone, 2016)
Nine male sterile lines and six pollinators were crossed in line x tester fashion to develop S4 single hybrids. The combining ability analysis revealed the significance of lines, testers and line x tester, indicating the presence of diversity among parents and hybrids. Contribution of line x tester was highly significant for all the characters. Non-additive gene effects were predominant for effective tillers whereas substantial additive gene effects were noted for days to flower and ear length. Al cytosterile system male sterile lines were found to be good general combiners for grain yield and dry fodder yield. Lines HMS lA, HMS 2A, HMS 9A and MS 81A combined significantly better for earliness. The testers 1CR 161, HTP 31, H 94/36 showed significantly positive GCA effects for grain yield as well as dry fodder yield.